The Association of Sociodemographic Factors with Health Literacy Among High-Risk Pregnant Women in Wetland Areas - Renny Aditya; Putri Indah Permata (Lambung Mangkurat University, 2025)
Abstract Enhancing quality of life, maternal mortality resulting from pregnancy-related complications should be avoided. Improving health literacy in pregnant women is a factor affecting maternal health status. The variety of socioeconomic circumstances results in high-risk pregnant women possessing low health literacy. Inadequate mother health literacy correlates with a rise in pregnancy problems. This study seeks to elucidate the health literacy of high-risk pregnant women and its association with sociodemographic characteristics in the wetland region of Banjarmasin City. This study employs a cross-sectional design with high-risk pregnant women who consented to participate in the survey (n=30). Participants were randomised using simple random sampling and instructed to complete a sociodemographic questionnaire along with the Maternal Health Literacy Inventory in Pregnancy (MHELIP). The chi-square test was employed for data analysis (SPSS 29). The principal endpoint of this study is the MHELP score for evaluating maternal health literacy. A total of 46.67% of participants (n=14) exhibited adequate literacy, 33.33% (n=10) shown good literacy, and 20% (n=6) had problematic literacy. A substantial correlation existed between educational attainment and maternal health literacy status (p<0.01). Nonetheless, no significant correlation was identified between other sociodemographic characteristics, including occupation (p=0.75), income (p=0.30), and parity (p=0.96), and maternal health literacy. The majority of high-risk pregnant women in this study possess sufficient health literacy. The education level is a sociodemographic variable significantly associated with the health literacy of high-risk pregnant women. The results suggest that enhancing maternal health literacy can be achieved through targeted educational initiatives. Consequently, initiatives aimed at enhancing health literacy among high-risk pregnant women should prioritise educational components to attain optimal outcomes.